The supervillain and me - Banas, Danielle (Swoon Reads, 2018)
Abby Hamilton's older brother moonlights as a superhero, but she has no interest in following in his footsteps--until a "supervillain" called Iron Phantom saves her life and warns her that not everyone in the "hero" world is who they seem to be. Now, Abby's the one who'll need to leap into action and save the day.